Education of Water Crisis Preparedness to Communities in Urban Slum Areas - Azyyati Ridha Alfian; Fea Firdani; Aulia Erid Angelica; Rifa Salsabila (Warta Pengabdian Andalas, 2024)
The availability of clean water is a significant factor in ensuring human survival. When there is insufficient water to supply a population adequately, we say there is a water shortage. The water issue is impacting several metropolitan regions worldwide, including Indonesia. In Padang, 22 sub-districts are included in the list of slum sub-districts, including Pasar Ambacang. The current condition requires more community preparedness to face the water crisis. People must be adequately prepared for water crises or be taught how to use available water supplies efficiently. Increasing knowledge about community preparedness in facing the water crisis is essential because increasing public knowledge will increase community preparedness in facing the water crisis. The effort was carried out by distributing leaflets and giving lectures door to door. This exercise increased the percentage of the community prepared to deal with the water situation before and after receiving instruction. It can lessen the number of potential dangers and casualties during a disaster. If the community is prepared, it will be easier to carry out rescue actions when a disaster occurs.